Is the facilitation of sustainable market access achievable? Design and implementationlessons from Armenia - Hamish Gow; Aleksan Shanoyan (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2010)
Over the past three decades the globalization in agri-food sector has been accompanied by a dramatic restructuring, liberalization and privatization of markets often with serious adverse consequences for small farmers in developing and transition countries. Consequently, governments and the international donor community have markedly shifted their development policies from traditional technology transfer approaches towards more market-driven approaches of linking farmers to markets. The international agricultural development literature has begun exploring the appropriate structure of third-party facilitated institutions and enforcement mechanisms to support linking small farmers to markets. Based upon a series of long-term qualitative and quantitative analyses of the instrumental case of USDA Marketing Assistance Project in Armenia, we use a grounded theory approach to develop a dual strategic model for the establishment of sustainable third party facilitated market linkages between producers and processors. Our results and model indicate that if donors pursue a dual strategy of concurrent facilitation of private enforcement on the processing level and institutional arrangement on the producer level in the design and implementation of third-party market linkage programs, they are likely to achieve higher program impact, improved trust among channel participants, and long-run economic sustainability of market linkages.
Keywords: 330; Market Linkages; Small Farmers; Institutions; Governance; Enforcement; Armenia